Three‐Phase Photocatalysis for the Enhanced Selectivity and Activity of CO2 Reduction on a Hydrophobic Surface. (4th September 2019) - Li, Ang; Cao, Qian; Zhou, Guangye; Schmidt, Bernhard V. K. J.; Zhu, Wenjin; Yuan, Xintong; Huo, Hailing; Gong, Jinlong; Antonietti, Markus
Abstract: The photocatalytic CO2 reduction reaction (CRR) represents a promising route for the clean utilization of stranded renewable resources, but poor selectivity resulting from the competing hydrogen evolution reaction (HER) in aqueous solution limits its practical applicability. In the present contribution a photocatalyst with hydrophobic surfaces was fabricated. It facilitates an efficient three‐phase contact of CO2 (gas), H2 O (liquid), and catalyst (solid). Thus, concentrated CO2 molecules in the gas phase contact the catalyst surface directly, and can overcome the mass‐transfer limitations of CO2, inhibit the HER because of lowering proton contacts, and overall enhance the CRR. Even when loaded with platinum nanoparticles, one of the most efficient HER promotion cocatalysts, the three‐phase photocatalyst maintains a selectivity of 87.9 %. Overall, three‐phase photocatalysis provides a general and reliable method to enhance the competitiveness of the CRR. Abstract : Die photokatalytische CO2 ‐Reduktion (CRR) in wässriger Lösung ist eine vielversprechende Reaktionroute, starke H2 ‐Erzeugung (HER) schränkt allerdings die Selektivität und Aktivität stark ein. Eine Strategie wurde entwickelt, um einen dreiphasigen Kontakt von CO2 (Gas), H2 O (Flüssigkeit) und Katalysator (Feststoff) herzustellen und so die Stofftransferlimitierung von CO2 zu überwinden, die CO2 ‐Konzentration auf der Katalysatoroberfläche zu erhöhen, HER zu unterdrücken und die Aktivität und Selektivität der CRR zu erhöhen.